Aplicación de soluciones nutritivas en variedades de lechuga en cultivo hidropónico bajo el sistema nft. - Cevallos Mendoza, Mario Ramiro (2020)
The project was carried out in the “El Paraíso” neighborhood, La Maná parish, La Maná canton, Cotopaxi province located at a height of 255 meters above sea level, latitude 00 ° 56´51.46 ”S and longitude 79 ° 13´40.61” W. This research was based on the "application of nutrient solutions in varieties of lettuce in hydroponic cultivation under the NFT system" which consisted of two 60-liter tanks with two 2-hp water pumps that independently carried out irrigation in PVC pipes. This research had as objectives the evaluation of some indicators of growth of the three varieties of lettuce, as well as the determination of the nutritious solutions applied, where the best response in the varieties was measured and the evaluation of the indicators of production of the same in hydroponic conditions. The factors studied were the three varieties of lettuce with the application of the two nutritive solutions, it was done with the NFT method (Nutrient Film Technique), as a result of the factors, six treatments were obtained each with three repetitions. A completely randomized block design (DBCA) was applied. The results of the interactions between the varieties and solutions at 60 days for: the number of leaves the Starfighter variety reacted better with the LM solution an average of 30, 67 leaves per plant, while the Patagonia variety with the LM solution obtained an average of 13.56 sheets; it was determined in the leaf length that the LM solution obtained better averages with the Starfighter variety obtaining 19.75 centimeters, however Patagonia with the LM solution obtained an average of 12.53 centimeters; as for the width of the leaves, the favorable results were obtained by Starfighter with the LM solution with 14.07 centimeters, on the contrary the Patagonia variety with the application of the T solution was low with only 6.06 centimeters; with respect to the root length an average of 20.45 centimeters was obtained by applying the LM solution to the Starfighter variety; On the other hand, Patagonia with the solution T obtained an average of 13.68 centimeters. Regarding the performance in the variable leaf weight, the Starfighter variety reacted in the same way with the two solutions; Regarding to the weight of the plant, the best average was obtained by the Starfighter variety and the LM solution, obtaining 24090 kg / ha.